In Vitro Gene Delivery with Large Porous Silicon Nanoparticles Fabricated Using Cost‐Effective, Metal‐Assisted Chemical Etching. Issue 3 (7th November 2016) - Wareing, Nancy; Szymanski, Kyle; Akkaraju, Giridhar R.; Loni, Armando; Canham, Leigh T.; Gonzalez‐Rodriguez, Roberto; Coffer, Jeffery L.
Abstract : The cytocompatibility, cell membrane affinity, and plasmid DNA delivery from surface oxidized, metal‐assisted stain‐etched mesoporous silicon nanoscale particles (pSiNPs) to human embryonic kidney (HEK293) cells is demonstrated, suggesting the possibility of using such material for targeted transfection and drug delivery.